The Contribution of Internal Audit to the Improvement of Internal Control System - Najah, El Azhary; Omar, Taouab (European Scientific Journal, ESJ, 2018)
In order to be more flexible in a perpetual mutational environment and face up to damaging effects of an economic situation in strong growth, organizations have to acquire efficient management tools allowing them to accomplish their objectives and to protect themselves against inherent risks. The implementation of an internal control system is considered to be the guarantor of an invincible organizational system and a means of control of risky operations. However, an applied and well conceived internal control provides the organization just a reasonable and not an absolute insurance about its objectives realization and sustainability. It is the reason for which an upper level control, accomplished by the internal audit function, seems to be a palliative to the internal control deficiencies, and a means of supervising and evaluating the application of procedures and internal control rules. Thus, this research aims at demonstrating how internal audit can participate to the improvement of internal control system. In this context, we have introduced a qualitative study, which was based on a sample of 10 Moroccan publicly traded companies that operate in many industries. Through the interviews conducted with this sample, we had identified firstly, the different control levels within organizations, and their degree of effectiveness and their capacity to face up risks as well as the limits of each type of control. Secondly, this research explored that internal audit is considered as a response to the insufficiencies of different lower control levels, and a means of monitoring and piloting the effectiveness of internal control system, across notably the recommendations provided.